Quasi-periodic behaviour in the optical and γ-ray light curves of blazars 3C 66A and B2 1633+38. Issue 4 (16th January 2020) - Otero-Santos, J; Acosta-Pulido, J A; Becerra González, J; Raiteri, C M; Larionov, V M; Peñil, P; Smith, P S; Ballester Niebla, C; Borman, G A; Carnerero, M I; Castro Segura, N; Grishina, T S; et al.
ABSTRACT: We report on quasi-periodic variability found in two blazars included in the Steward Observatory Blazar Monitoring data sample: the BL Lac object 3C 66A and the Flat Spectrum Radio Quasar B2 1633+38. We collect optical photometric and polarimetric data in V and R bands of these sources from different observatories: St. Petersburg University, Crimean Astrophysical Observatory, WEBT–GASP, Catalina Real-Time Transient Survey, Steward Observatory, STELLA Robotic Observatory, and Katzman Automatic Imaging Telescope. In addition, an analysis of the γ-ray light curves from Fermi –LAT is included. Three methods are used to search for any periodic behaviour in the data: the Z-transform Discrete Correlation Function, the Lomb–Scargle periodogram and the Weighted Wavelet Z-transform. We find pieces of evidence of possible quasi-periodic variability in the optical photometric data of both sources with periods of ∼3 yr for 3C 66A and ∼1.9 yr for B2 1633+38, with significances between 3σ and 5σ. Only B2 1633+38 shows evidence of this behaviour in the optical polarized data set at a confidence level of 2σ–4σ. This is the first reported evidence of quasi-periodic behaviour in the optical light curve of B2 1633+38. Also, a hint of quasi-periodic behaviour is found in the γ-ray light curve of B2 1633+38 with a confidence level ≥2σ, while no periodicity is observed for 3C 66A in this energy range. We propose different jet emission models that could explain the quasi-periodic variability and the differences found between these two sources.